Kolektivne tožbe kot novo pravno sredstvo zoper množične kršitve pravic iz delovnopravnih razmerij - Vlahek, Ana (Delavci in delodajalci, 2018)
Slovenian Collective Actions Act (CAA) that began to apply on 21 April 2018 provides for collective settlements and collective actions in areas where mass damages are most common. In cases of violations of workers' rights many individuals may be harmed in an essentially similar way. The CAA thus applies also to claims by workers whose rights would otherwise have to be enforced through individual lawsuits in the so-called individual labor disputes. The article analyzes the basic solutions of the CAA and highlights the specifics applicable to labor disputes, and presents the framework of the collective damages action procedure.
Keywords: collective action; kolektivna tožba; kolektivno varstvo pravic delavcev; protection of employees' rights in collective court and settlement proceedings; Register kolektivnih tožb; Slovenian Collective Actions Act; zakon o kolektivnih tožbah